1993
DOI: 10.1115/1.2929268
|View full text |Cite
|
Sign up to set email alerts
|

Separated Flow in a Low-Speed Two-Dimensional Cascade: Part I—Flow Visualization and Time-Mean Velocity Measurements

Abstract: This study was conducted for the purpose of providing a more fundamental understanding of separated flow in cascades and to provide performance data for fully stalled blade rows. Cascades of a single blade geometry and a solidity of unity were studied for three stagger angles and the full range of angle of attack, extending well into the stalled flow regime. Results are presented from flow visualization and time-mean velocity measurements of stalled flow in the cascade. Surface and smoke flow visualization rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The stagger angle was kept at 51· and only the incidence angle was varied from -40· to 20· by rotating the turning table. Thus, the effect of the stagger angle was not explored in the present research even though its effect on the performance of a cascade is significant as Yocum and O'Brien (1993) claimed. The blade is a double circular airfoil with blade height of 20 em.…”
Section: Flow Condition and Grid Testmentioning
confidence: 96%
See 1 more Smart Citation
“…The stagger angle was kept at 51· and only the incidence angle was varied from -40· to 20· by rotating the turning table. Thus, the effect of the stagger angle was not explored in the present research even though its effect on the performance of a cascade is significant as Yocum and O'Brien (1993) claimed. The blade is a double circular airfoil with blade height of 20 em.…”
Section: Flow Condition and Grid Testmentioning
confidence: 96%
“…Sovran (1959) reported that for conditions when rotating stall occurred, the phenomena closely resemble a Karman vortex street. Yocum and O'Brien (1993) presented flow visualization and time-mean velocity characteristics of stalled flow in a cascade. They suggested that the flow of a larger stagger cascade is more easily diverted around the separation region, resulting in the separated region extending further into the blade passage.…”
Section: Introductionmentioning
confidence: 99%
“…For a compressor it occurs at the junction of the end-wall and the blade suction side. The corner separation has been investigated experimentally on linear compressor cascades [3,4,2,5], and numerically [6], but its physics is not yet entirely understood.…”
Section: Introductionmentioning
confidence: 99%